Apomixis for cultivar development in tropical forage grasses - Miles, John W. (Wiley, 2007)
Apomixis—asexual reproduction through seed—provides a convenient means to faithfully propagate even heterozygous genotypes and hence exploit heterosis, in several naturally apomictic, warm-season forage grasses. Inheritance of apomixis has been shown to be monogenic dominant in at least four economically important panacoid grasses. Previously proposed breeding schemes for apomicts do not provide a means to accumulate genes contributing to nonadditive, heterotic effects over cycles of selection and recombination. Following the development of successful brachiariagrass [Brachiaria (Trin.) Griseb] cultivars by ecotype selection, artificial hybridization of brachiariagrasses began in the late 1980s with the development of a sexual tetraploidized biotype of the natural diploid, sexual ruzigrass (Brachiaria ruziziensis Germain and Evrard). A breeding scheme—recurrent selection for specific combining ability—designed to accumulate nonadditive effects, originally proposed for sexual maize (Zea mays L.), is suggested as an appropriate scheme for improvement of apomictic tropical grasses. Recurrent selection on specific combining ability or interpopulation selection schemes such as reciprocal recurrent selection should be appropriate for other asexually propagated crops.